The Changing Perception and Buying Behavior of Women in Kathmandu Valley - Bhusal, Sakshi (Nepalese Journal of Economics, 2025)
This study examines the factors influencing the changing perception and buying behavior of women in Kathmandu valley. Buying behavior of women and changing perception of women are the selected dependable variable. The selected independent variables are psychological factor, economic factor, perceived value, brand image and perceived usefulness. The primary source of data is used to assess the opinions of the respondents regarding the changing perception and buying behavior of women in Kathmandu valley. The study is based on primary data of 154 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and different factors influencing the changing perception and buying behavior of women in Kathmandu valley. The study showed that psychological factor has a positive impact on buying behavior of women and changing perception of women. It indicates that increase in psychological factor leads to increase in buying behavior of women and changing perception of women. Likewise, economic factor has a positive impact on changing perception of women and buying behavior of women. It indicates that increase in economic factor leads to increase in changing perception of women and buying behavior of women. Similarly, perceived value has a positive impact on buying behavior and changing perception of women. It means that perceived value in the organization leads to increase in buying behavior of women and changing perception of women. Moreover, brand image has a positive impact on buying behavior of women and changing in perception of women. It indicates that better the brand image, higher would be the buying behavior of women and changing perception of women. In addition, perceived usefulness has a positive impact on buying behavior of women and changing perception of women. It reveals that most effective perceived usefulness leads to increase in buying behavior of women and changing perception of women.